166k views
3 votes
PLEASE HELP ASAP

Write the expression as a product of polynomials

1) y(a–c)+5a–5c

2) x(b+c)+3b+3c

User Andreina
by
5.2k points

2 Answers

4 votes

Hello from MrBillDoesMath!

Answer:

1. (a-c) (y + 5)

2. (b+c)(x+3)


Discussion:

1.

y(a-c) + 5a - 5c => factor 5 from the second expression

= y(a-c) + 5 (a-c) => factor (a-c) from each term

= (a-c) (y + 5)



2

x(b+c) + 3b + 3c => factor 3 from the second expression

= x(b+c) + 3 (b+c) => factor (b+c) from each term

= (b+c)(x+3)



Thank you,

MrB

User QTom
by
6.6k points
4 votes

Answer to Q1

(a-c)(y+5)

Explanation:

Given expression is

y(a-c)+5a-5c

we observe that 5 is common in above expression

y(a-c)+5(a-c)

Now, take (a-c) as common

(a-c)(y+5) which is the product of polynomials.

Answer to Q2:

(b+c)(x+3)

Explanation:

Given expression is

x(b+c)+3b+3c

3 is common in above factor so ,

x(b+c)+3(b+c)

Now, take (b+c) as common

(b+c)(x+3) which is the product of polynomials.




User RickardSjogren
by
5.9k points